Reducing harm through the development of good preparation practices for the injection of slow release morphine sulphate capsules - Lenneke Keijzer (BMC, 2020)
Abstract Background It is not always easy to advise people who inject drugs (PWID) on how to prepare their drugs in a way that is associated with reduced harm. This is particularly true for pharmaceutical drugs that are not meant to be injected. Our objective was to find "good preparation practices" for slow release morphine sulphate capsules, namely preparation methods that reduce harm, that are evidence-based and acceptable to PWID. Methods In the laboratory, morphine sulphate capsules were prepared using both a cold and lukewarm preparation technique, two contact and stirring durations (1 min and 20 s) and 4 different filters (cotton filter, Sterifilt, Sterifilt+ and a wheel filter). The following outcomes were compared: particle reduction and morphine content in the filtrate, as well as filtration ease and time. Results The lukewarm method and a stirring and contact time of 1 min were associated with a considerably higher morphine yield than both the cold method and the stirring time of only 20 s. Moreover, the suspension obtained was easy to filter using membrane filters. Particle reduction was important with all three membrane filters tested. Using the lukewarm method, morphine recovery was 86% for the wheel filter, 89% for the Sterifilt and 99% for the Sterifilt+. Conclusions The provision of a method that is easy to use, reduces harms associated to the injection of insoluble particles and recovers virtually all the active drug has a large chance to be adopted by people who use drugs. This type of "best practices" can be provided by drug workers and by people who use drugs to actively promote harm reduction.